Improved evaluation of inelastic displacement demands for short‐period masonry structures. (20th January 2017) - Guerrini, Gabriele; Graziotti, Francesco; Penna, Andrea; Magenes, Guido
Summary: This work discusses the simplified estimation of earthquake‐induced nonlinear displacement demands as required by nonlinear static procedures, with particular attention on short‐period masonry structures. The study focuses on systems with fundamental periods between 0.1 and 0.5 s, for which inelastic amplification of the elastic displacement demand is more pronounced; hysteretic force‐displacement relationships characteristic of masonry structures are adopted, because these structures are more commonly found within the considered period range. Referring to the results of nonlinear dynamic analyses of single‐degree‐of‐freedom oscillators, some limitations of the Eurocode 8 and Italian Building Code formulations are first discussed, then an improved equation is calibrated that relates inelastic and elastic displacement demands. Numerical values of the equation parameters are obtained, considering the amount of hysteretic energy dissipation associated with various damage mechanisms observed in masonry structures. Safety factors are also calculated to determine several percentiles of the displacement demand. It is shown that the proposed equation can be extended to more dissipative systems. Finally, the same formulation is adapted to the estimation of seismic displacements when elastic analysis procedures are employed. Copyright © 2017 John Wiley & Sons, Ltd.